Understanding art : a guide for teachers - Wenham, Martin (SAGE, 2003)
Martin Wenham explores the basic knowledge that children need to know in order to explore and experiment with the visual language that artists use to communicate. The National Curriculum places a strong emphasis on experimenting with and applying the visual elements.